INTERNAL AND EXTERNAL FACTORS THAT INFLUENCE EARNINGS MANAGEMENT - Ni Putu Tiara Maharani Krisna Putri; Komang Ayu Sintha Trisnayuni; Ni Nyoman Ayu Suryandari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
Earnings management is a manager's effort to influence financial report information to deceive stakeholders. This research aims to obtain empirical evidence of the influence of external factors (audit quality) and internal factors (audit committee, leverage, and company size) on earnings management. The research population is manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The sample was 54 companies based on the purposive sampling method. The analysis technique in this research is multiple linear regression. The research results show that audit quality has a positive effect on earnings management. Company size has a negative effect on earnings management. Meanwhile, the audit committee and leverage do not affect earnings management. Future research can develop this research by testing it at other research locations.